Reducing US Cancer Burden and Disparities Through National and Targeted Food Price Policies (P04-101-19). (13th June 2019) - Eom, Heesun; Wilde, Parke; Cudhea, Frederick; Du, Mengxi; Michaud, Dominique; Wong, John; Mozaffarian, Dariush; Zhang, Fang Fang
Abstract: Objectives: Disparities in cancer among low-income Americans in the Supplemental Nutrition Assistance Program (SNAP) are well documented. While policies to alter food prices (taxes, subsidies) have demonstrated success at changing dietary intakes, the effectiveness of these policies on reducing cancer burdens and disparities has not been quantified. We aimed to evaluate the effectiveness of population strategies on reducing US cancer burdens and disparities through national or targeted food price policies. Methods: A Comparative Risk Assessment (CRA) model was used to assess the effectiveness of 9 different potential policies for reducing cancer burden and disparity among US adults in 2015. These included (1) 5 policies with varying levels (10%, 30%) of subsidies on fruits, vegetables, and whole grains, with and without 10% taxes on sugar-sweetened beverages and processed meats for the general US population, (2) a targeted 30% subsidy in SNAP, and (3) combinations of the general policies and targeted SNAP policy. Data inputs included national demographic and dietary data on the US adult population and SNAP participants from the National Health and Nutrition Examination Survey 2009–2014, cancer incidence from the Surveillance, Epidemiology and End Results (SEER), and policy effects and diet-cancer effects from meta-analyses. Cancer disparities were quantified as the difference in cancer incidence between SNAP participants and higher-income individuals. Uncertainty in each parameter was jointly incorporated using probabilistic sensitivity analysis (PSA) with 1000 simulations. Results: All policies reduced cancer burdens, with between ∼5 to 40 new cases per million adults prevented annually (Figure 1 ). The national 30% subsidy +10% tax produced largest overall benefits, averting an estimated 6875 new cancer cases (28 cases per million US adults) per year. The 10% national tax +30% SNAP-targeted food subsidies produced the largest reduction in cancer disparities (14 more cases averted per million among SNAP vs. higher-income individuals) (Figure 2 ). Conclusions: All national food price policies meaningfully reduced cancer burdens, while SNAP-targeted food price policies, alone or in combination with national policies, reduced cancer disparities. Funding Sources: This study was supported by NIH/NIMHD. Supporting Tables, Images and/or Graphs: